Are people who do yoga any better at a motor imagery task than those who do not?. Issue 2 (15th December 2012) - Wallwork, Sarah B; Butler, David S; Wilson, Dianne J; Moseley, G Lorimer
Abstract : Background: Yoga is a popular recreational activity in Western society and there is an abundance of literature suggesting that yoga may be beneficial for people with a chronic pain disorder. Despite consistently positive results in the literature, the mechanisms of effect are unclear. On the grounds that chronic pain is associated with disruptions of brain-grounded maps of the body, a possible mechanism of yoga is to refine these brain-grounded maps. A left/right body part judgement task is an established way of interrogating these brain-grounded maps of the body. Objective: To determine if people who do regular yoga practice perform better at a left/right judgement task than people who do not. Methods: Previously collected, cross-sectional data were used. Using a case–control design, participants who reported taking part in regular yoga were selected against age, gender, neck pain and arm pain-matched controls. Participants viewed 40 photographs of a model with their head turned to the left or right, and were asked to judge the direction of neck rotation. They then completed a left/right-hand judgement task. Results: Of the 1737 participants, 86 of them reported regularly taking part in yoga. From the remaining participants, 86 matched controls were randomly selected from all matched controls. There was no difference between Groups (yoga and no yoga) for either response time (p=0.109) or accuracy (p=0.964). There was a difference between Tasks; people were faster (p<0.001) and more accurate (p=0.001) at making left/right neck rotation judgements than they were at making left/right-hand judgements, regardless of group. Conclusions: People who do regular yoga perform no differently in a left/right judgement task than people who do not.